Modulating factors of hydrologic exchanges in a large‐scale river reach: Insights from three‐dimensional computational fluid dynamics simulations. Issue 23 (9th October 2018) - Bao, Jie; Zhou, Tian; Huang, Maoyi; Hou, Zhangshuan; Perkins, William; Harding, Samuel; Titzler, Scott; Hammond, Glenn; Ren, Huiying; Thorne, Paul; Suffield, Sarah; Murray, Christopher; et al.
Abstract: Hydrologic exchange is a critical mechanism that shapes hydrological and biogeochemical processes along a river corridor. Because of limitations in field accessibility, computational demand, and complexities of geomorphology and subsurface geology, full three‐dimensional modelling studies to quantify hydrologic exchange fluxes (HEFs) have been limited mostly to local‐scale applications. At reach scales, although surface flow conditions and subsurface physical properties are well‐known factors that modulate hydrologic exchanges, quantitative measures that can describe the effects of these factors on the strength and direction of such exchanges do not exist. To address this issue, we developed a one‐way coupled surface and subsurface water flow model using the commercial computational fluid dynamics (CFD) software STAR‐CCM+ and applied it to simulate HEFs in a 7‐km long reach along the main stem of the Columbia River in the United States. The model was validated against flow velocity measurements from an acoustic Doppler current profiler in the river, vertical HEFs estimated from a set of temperature profilers installed across the riverbed, and simulations from a reactive transport model. The validated model then was employed to systematically investigate how HEFs could be influenced by surface water fluid dynamics, subsurface structures, and hydrogeological properties. Our results suggest that reach‐scale HEFs are dominated primarily by the thickness of the riverbed alluvium layer, and then by the alluvium permeability, the depth of the underlying impermeable layer, and the pressure boundary condition. Our results also elucidate the scale dependence of HEFs on fluid dynamics that can be captured only by three‐dimensional CFD models. That is, while the net HEFs over the entire 7‐km domain are not significantly influenced by surface water dynamics pressure, the dynamic pressure induced by fluid dynamics can lead to more than 15% in net HEFs for a river section of a few hundred metres.